Decentralized coordinated control of elastic web winding systems without tension sensor. (September 2018) - Hou, Hailiang; Nian, Xiaohong; Chen, Jie; Xiao, Dengfeng
Abstract: In elastic web winding systems, precise regulation of web tension in each span is critical to ensure final product quality, and to achieve low cost by reducing the occurrence of web break or fold. Generally, web winding systems use load cells or swing rolls as tension sensors, which add cost, reduce system reliability and increase the difficulty of control. In this paper, a decentralized coordinated control scheme with tension observers is designed for a three-motor web-winding system. First, two tension observers are proposed to estimate the unwinding and winding tension. The designed observers consider the essential dynamic, radius, and inertial variation effects and only require the modest computational effort. Then, using the estimated tensions as feedback signals, a robust decentralized coordinated controller is adopted to reduce the interaction between subsystems. Asymptotic stabilities of the observer error dynamics and the closed-loop winding systems are demonstrated via Lyapunov stability theory. The observer gains and the controller gains can be obtained by solving matrix inequalities. Finally, some simulations and experiments are performed on a paper winding setup to test the performance of the designed observers and the observer-base DCC method, respectively. Highlights: Two tension observers are designed for a web-winding system. A decentralized coordinated control without tension sensors is proposed. The matrix inequality method has been used to compute the controller gains and observer gains. Simulations and experiments have been carried out to investigate the performance of the observer and the proposed controller.